Study protocol: treatment with caffeine of the very preterm infant in the delivery room: a feasibility study. Issue 12 (4th December 2020) - Dani, Carlo; Cecchi, Alessandra; Remaschi, Giulia; Mercadante, Domenica; la Marca, Giancarlo; Boni, Luca; Mosca, Fabio
Abstract : Introduction: Early treatment with caffeine in the delivery room has been proposed to decrease the need for mechanical ventilation (MV) by limiting episodes of apnoea and improving respiratory mechanics in preterm infants. Thus, the purpose of this feasibility study is to verify the hypothesis that intravenous or enteral administration of caffeine can be performed in the preterm infant in the delivery room. Methods and analysis: In this multicentre prospective study, infants with 25 +0 –29 +6 weeks of gestational age will be enrolled and randomised to receive 20 mg/kg of caffeine citrate intravenously, via the umbilical vein, or enterally, through an orogastric tube, within 10 min of birth. Caffeine plasma level will be measured at 60±15 min after administration and 60±15 min before the next dose (5 mg/kg). The primary endpoint will be evaluation of the success rate of intravenous and enteral administration of caffeine in the delivery room. Secondary endpoints will be the comparison of success rate of intravenous versus oral administration and the evaluation of the need for MV in treated infants. In the absence of previous references, we arbitrarily decided to study 20 infants treated with intravenous caffeine and 20 infants treated with enteral caffeine. Primary endpoint will be evaluated measuring the success rate of intravenous and enteral caffeine administration which will be considered a success when it is followed by the achievement of the caffeine therapeutic level (8–25 µg/mL) 60±15 min before administration of the second dose. Ethics and dissemination: The study has been approved by the Italian Medicines Agency (AIFA: AIFA/RSC/P/32755) and by Comitato Etico Pediatrico Regione Toscana. The results will be published in peer-reviewed academic journals. Trial registration number: ClinicalTrials.gov identifier NCT04044976 ; EudraCT number 2018-003626-91.